Research on geography teaching: analyzing the 'capixaba' meetings of geography - Dalapicola, Tiago; Oliveira, Regina de Marchi Lyra (Geosaberes, 2018)
The article deals with the insertion of contents pertinent to the teaching of Geography in the 'Capixaba' Meetings of Geography, in the wake of the resurgence of the local section of the Association of Brazilian Geographers in that state. It was based, for such, in documentary analysis and literature review on the importance of the research for teacher training. The research concluded that by the time of the organization of the four events held, althought the career of teacher was a most sought modality and with greater offer of vacancies in the courses of Geography of the state, the subject of teaching was inserted in the events as residual and underrepresented.